2016
DOI: 10.1371/journal.pone.0162645
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Patients with Helicobacter pylori Infection and the Subsequent Risk of Developing Osteoporosis after Eradication Therapy: A Nationwide Population-Based Cohort Study

Abstract: PurposePrevious studies have reported conflicting results on the association between Helicobacter pylori infection and osteoporosis. A few studies have discussed the influence of H. pylori eradication therapy on bone mineral density.MethodsWe assessed the prevalence of osteoporosis among the H. pylori-infected population in Taiwan and the influence of early and late H. pylori eradication therapy on bone mineral density.ResultsUsing data from Taiwan's National Health Insurance Research Database, we identified 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…H. pylori infection causes chronic gastritis and induces a permanent inflammatory response that may increase both the gastric and the systemic indexes of inflammation, such as TNF- α , IL-1, and IL-6 [ 35 ]. Shih et al demonstrated that H. pylori infection may be associated with an increased risk of developing osteoporosis in elderly female patients with upper gastrointestinal diseases [ 36 ]. Meantime, Figura et al found that H. pylori infection by strains expressing CagA may be considered a risk factor for osteoporosis in men [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection causes chronic gastritis and induces a permanent inflammatory response that may increase both the gastric and the systemic indexes of inflammation, such as TNF- α , IL-1, and IL-6 [ 35 ]. Shih et al demonstrated that H. pylori infection may be associated with an increased risk of developing osteoporosis in elderly female patients with upper gastrointestinal diseases [ 36 ]. Meantime, Figura et al found that H. pylori infection by strains expressing CagA may be considered a risk factor for osteoporosis in men [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 A very interesting safety study looked at any association between H. pylori eradication therapy and the development of osteoporosis, a highly relevant topic in the context of recent data linking PPI use to osteoporosis. 12 An increase in the risk of developing osteoporosis was found to be higher in the early H. pylori treatment (within 1 year of diagnosis) cohort and also in the late H. pylori treatment cohort, compared with controls; however, when the follow-up period was over 5 years, only the late eradication group exhibited a higher incidence of osteoporosis. This may imply that early eradication could reduce any potential influence of H. pylori infection on osteoporosis either directly or by reducing PPI use.…”
Section: Triple Therapymentioning
confidence: 83%
“…In terms of safety, a Japanese study of 322 patient showed a 15% incidence of diarrhea and 2% risk of skin rash . A very interesting safety study looked at any association between H. pylori eradication therapy and the development of osteoporosis, a highly relevant topic in the context of recent data linking PPI use to osteoporosis . An increase in the risk of developing osteoporosis was found to be higher in the early H. pylori treatment (within 1 year of diagnosis) cohort and also in the late H .…”
Section: Triple Therapymentioning
confidence: 99%
“…Although H. pylori infection causing a decrease in bone density is supported by most researchers, the effect of early eradication therapy is still insu cient. Replogle ML holds the view that early eradication therapy may eliminate chronic in ammation from H. pylori 37 . Some articles have also reported an improvement in B12 levels after complete eradication 13,38 , which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%